2017
DOI: 10.1016/j.jbiotec.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

High-content analysis screening for cell cycle regulators using arrayed synthetic crRNA libraries

Abstract: The CRISPR-Cas9 system has been utilized for large-scale, loss-of-function screens mainly using lentiviral pooled formats and cell-survival phenotypic assays. Screening in an arrayed format expands the types of phenotypic readouts that can be used to now include high-content, morphology-based assays, and with the recent availability of synthetic crRNA libraries, new studies are emerging. Here, we use a cell cycle reporter cell line to perform an arrayed, synthetic crRNA:tracrRNA screen targeting 169 genes (>60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…For this reason, an important prerequisite for these screens would be to be able to transfect low number of cells with minimal cytotoxicity. We have observed that with liquid transfection some cell lines such as RPE‐1 can be efficiently transfected when low number of cells was seeded (2,500 cells/well) as previously reported in the literature for other cell lines (Tan & Martin, ; Strezoska et al , ; de Groot et al , ). However, some cell lines such as NCI‐H358, NCI‐N87, or HEK293T that also express doxycycline‐inducible Cas9 (Fig EV1) suffer from increased cytotoxicity and high variability under the same conditions.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…For this reason, an important prerequisite for these screens would be to be able to transfect low number of cells with minimal cytotoxicity. We have observed that with liquid transfection some cell lines such as RPE‐1 can be efficiently transfected when low number of cells was seeded (2,500 cells/well) as previously reported in the literature for other cell lines (Tan & Martin, ; Strezoska et al , ; de Groot et al , ). However, some cell lines such as NCI‐H358, NCI‐N87, or HEK293T that also express doxycycline‐inducible Cas9 (Fig EV1) suffer from increased cytotoxicity and high variability under the same conditions.…”
Section: Resultssupporting
confidence: 74%
“…In summary, we developed a solid‐phase reverse transfection method that allows efficient delivery of either synthetic gRNAs or Cas9 containing RNP complexes. Our system has several advantages over previous delivery approaches for screening purposes (Tan & Martin, ; Bulkescher et al , ; Strezoska et al , ). First, the transfection complexes can be easily and efficiently coated onto the plates, and ready‐to‐use plates allow flexibility in designing experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This arrayed screening strategy allows detailed, image‐based phenotyping of populations of cells in which specific genes are perturbed (Boutros et al , ; Liberali et al , ; Caicedo et al , ). Recently, a number of studies have applied the CRISPR‐Cas9 system to an arrayed format, but these were limited in scale and only obtained well‐averaged readouts with low information content (Hultquist et al , ; Tan & Martin, ; Strezoska et al , ), not realizing the full potential that image‐based multivariate single‐cell phenotypic profiling could bring. Importantly, CRISPR‐Cas9 is not 100% effective in all targeted cells, which can be the result of in‐frame repair of the CRISPR‐Cas9‐induced DNA lesions, a failure to target all functional alleles or limited efficacy of the CRISPR‐Cas9 system (Shalem et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Some groups have previously attempted to develop arrayed CRISPR screens (Hultquist et al 2016;McCleland et al 2016;Tan and Martin 2016;Datlinger et al 2017;Strezoska et al 2017). These studies were based on guide RNA libraries consisting of individual lentiviral sgRNAs for single genes or synthesized CRISPR RNA (crRNA) in a manner similar to siRNA screens.…”
mentioning
confidence: 99%